Imaging of eye with OCT for disease diagnosis - Zhang, Yuxin (Nanyang Technological University, 2022)
Optical coherence tomography (OCT) is a high resolution clinical imaging tool for in vivo ocular imaging. This paper describes the details of OCT imaging, including resolution influencing factors, various OCT-based techniques, and the methods used in optical coherence tomography angiography (OCTA). To visualize fundus details, two algorithms for OCT fundus imaging are described in this paper. Optical microangiography based on Fourier-domain OCT can provide dynamic blood flow imaging of microcirculatory tissue beds in vivo. Split-spectrum amplitude-decorrelation angiography can overcome the limitation that OCT is sensitive to pulsatile bulk motion noise in the axial direction, thus improving the signal-to-noise ratio of blood flow detection. In this study, both algorithms are used on a sample of human tissue imaging, and the results are analyzed and discussed. At the end of this paper, a comparison of these two algorithms is provided and based on it, suggestions are made that can combine the two algorithms to better utilize their respective advantages.